Penerapan Media Audio Visual dalam Meningkatkan Kemampuan Menyimak pada Peserta Didik Kelompok B di RA Baitussa’adah Sadengrejo Rejoso Pasuruan (PROCEEDING: The Annual International Conference on Islamic Education, 2018)
Listening skills to hold an important role in a child's life because the listening skills we can deliver a thing. Based on the observations of researchers in RA Baitussaâ€™adah Sadengrejo Rejoso Pasuruan.  Particular grouped B contained some children who were not optimal in noticing it, because of the lack of attention to children in participating in learning activities so that researchers use Classroom Action Research as a research approach in order to enhance the child's ability to listen .. This study is an action research conducted with 2 cycles. In the study conducted using prasiklus three stages, the first cycle and second cycle to obtain the desired results. In prasiklus most children still scored an average of 31.26% while the percentage value in the first cycle increased by 25.4% to obtain the percentage becomes 56.66% which means it is still less than the maximum. After doing research on this second cycle average value of 80.42% child be so of the average grades in cycle I to cycle II was increased again by 23.75%. It can be seen in the comparison between the first cycle and second cycle during the study. From the results obtained which proves that there is an increase in the use of audio-visual media can enhance the listening skills of children.